Electrophysiological study on limb myokymia in three women. Issue 7 (July 1987) - Hosokawa, S; Shinoda, H; Sakai, T; Kato, M; Kuroiwa, Y
Abstract : Physiological studies on three women with limb myokymia were carried out. The patients had diabetic neuropathy, neuromyotonia, and autonomic polyneuropathy, respectively. The EMG discharge pattern, coincident with myokymia, in a patient with myokymia and neuromyotonia differed from those with myokymia without neuromyotonia. In only the first patient did the electrical stimulation of nerves evoke "late repetitive response" (LRR), which resembled the wave forms of the myokymic discharge. Epidural and peripheral nerve blocks abolished myokymia in the first and second cases, but peripheral nerve block was without effect in the third patient. These findings indicate that myokymia originates in multiple sites of alpha motor neurons and that the pathophysiology may vary.